Pallenopsis patagonica (Hoek, 1881) – a species complex revealed by morphology and DNA barcoding, with description of a new species of Pallenopsis Wilson, 1881. (14th January 2014) - Weis, Andrea; Meyer, Roland; Dietz, Lars; Dömel, Jana S.; Leese, Florian; Melzer, Roland R.
Abstract: Pallenopsis patagonica (Hoek, 1881) is one of the most taxonomically problematic and variable pycnogonid species, and is distributed around the southern South American coast, and the Subantarctic and Antarctic areas. We conducted a phylogenetic analysis of mitochondrial cytochrome c oxidase subunit I ( COI ) sequences of 47 Pallenopsis specimens, including 39 morphologically identified as P. patagonica, five Pallenopsis pilosa (Hoek, 1881), one Pallenopsis macneilli Clark, 1963, one Pallenopsis buphtalmus Pushkin, 1993, and one Pallenopsis latefrontalis Pushkin, 1993 . Furthermore, we studied morphological differences between the different COI lineages using light and scanning electron microscopy, including also material from Loman's and Hedgpeth's classical collections, as well as Hoek's type material of P. patagonica from 1881. The molecular results unambiguously reveal that P. patagonica is a complex of several divergent clades, which also includes P. macneilli, P. buphtalmus, and P. latefrontalis. Based on the material available, two major clades could be identified, namely a 'Falkland' clade, to which we assign the nominal P. patagonica, and a 'Chilean' clade, which is distinct from the 'Falkland' clade. We describe the 'Chilean' clade as new species, P allenopsis yepayekae sp. nov. Weis, 2013. All molecular results are confirmed by specific morphological characteristics that are discussed in detail and compared with Pallenopsis species closely related to the P. patagonica complex. Our results reveal that P. patagonica is a species-rich complex that is in need for a thorough taxonomic revision, using both morphological and genetic approaches. © 2014 The Linnean Society of London